Crimea in War and Transformation. - Kozelsky, Mara.
1 online resource (297 pages)
Keywords: Crimea in War and Transformation is the first exploration of the civilian experience during the Crimean War to appear in English. Beginning with Russian mobilization in 1852 and lasting through demobilization in 1857, the conflict devastated the peoples and landscapes of Crimea as well as the volatile southern borderlands of the Russian Empire, leading to the largest war recovery program yet undertaken by the Russian government.